THU0642 Living in immigrant communities does not impact total knee arthroplasty outcomes: experience from a high-volume centre in the united states. (12th June 2018) - Mehta, B.; Szymonifka, J.; Dey, S.A.; Navarro-Millan, I.Y.; Grassia, S.V.; Mandl, L.A.; Bass, A.R.; Russell, L.A.; Parks, M.L.; Figgie, M.P.; Lee, Y.-Y.; Nguyen, J.T.; et al.
Abstract : Background: Social factors affect TKA outcomes in osteoarthritis, both at the individual and neighbourhood level. 1 However, prior studies have not evaluated the influence of the proportion of immigrants within a neighbourhood, as reported for other high-volume and high-cost procedures. 2 Objectives: Our objective was to determine the association of neighbourhood immigrant proportion (IP) on Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and function scores at baseline and 2 years after elective TKA, and to examine if this is different between sexes. Methods: Individual patient-level variables were obtained from a single institution TKA registry between May 2007 and February 2011, including demographics, baseline and 2 year WOMAC pain and function (0–100; 100 best), and geocodable US addresses. We only included patients living in the tri-state area - i.e. New York, Connecticut and New Jersey which is the catchment area for the hospital. Individual patient level variables were then linked to US Census Bureau data at the census tract level. Data was analysed using univariate and multivariable linear mixed effects models, with census tracts variables treated as random effects. A separate linear mixed-effects model was used to assess the interaction between neighbourhood IP and gender. Results: Table 1 describes the 3, 898 TKA cases analysed. In multivariable analyses, patients from neighbourhoods with low IP (<10%) had slightly higher baseline and 2 year WOMAC pain and function scores than those with high IP (≥40%), but these differences were not statistically significant (table 2). While women had worse baseline and 2 year WOMAC pain and function scores (all p≤0.04), this difference was not significantly influenced by neighbourhood IP (all pinteraction NS). Table 2 Impact of neighbourhood immigrant proportion (IP) on WOMAC pain and function. Conclusions: Patients coming from high (>40%) IP neighbourhoods present with worse baseline pain and function. Two years later, worse pain and function persist; however, the difference is not significant. Although sex differences favouring males are notable, these differences are not associated with IP. Social factor contributions to healthcare disparities are multidimensional, and future studies examining immigration-related neighbourhood characteristics may be warranted. References: [1] Goodman SM, et al. Disparities in TKA Outcomes... Clin Orthop Relat Res2016. [2] Mojica CM, et al. The Relationship between Neighborhood Immigrant Composition... Biomed Res Int2015:460181. Disclosure of Interest: B. Mehta: None declared, J. Szymonifka: None declared, S. Dey: None declared, I. Navarro-Millan: None declared, S. Grassia: None declared, L. Mandl Grant/research support from: Boehringer-Ingelheim, A. Bass Grant/research support from: Abbott, Pfizer, L. Russell: None declared, M. Parks Grant/research support from: Zimmer, Consultant for: Zimmer, M. Figgie Shareholder of: Mekanika, Y.-Y. Lee: None declared, J. Nguyen: None declared, S. Goodman: None declared